Letter (copy) : Food for Spain - Tewson, Vincent
032-0114-001 International. HVT/EAB/AT/507. 1st February, 1939. Mr. W. Schevenels, International Federation of Trade Unions, 9 avenue d'Orsay, Paris, VII. Dear Comrade Schevenels, FOOD FOR SPAIN We have today learned from the Co-operative Wholesale Society that they have a steamer sailing for Rouen tomorrow, Thursday, 2nd February, and in view of the fact that you have already instructed the C.W.S. Rouen office to deliver the consignment of 14,278 bags of potatoes to Spain via Cerbere, we have asked them to ship the outstanding 674 bags of potatoes by this steamer. This latter consignment will complete the total of 750 tons. We have also asked the C.W.S. to instruct their Rouen office to keep in touch with you if any difficulty should arise and to act upon your instructions. Yours sincerely, Assistant Secretary. 292/946/32/114